Comparative evaluation of biofloc and aquamimicry systems : energy fluxes affecting biocolloids, sludge and growth of fish - Wanutsanan Pantachai; Salin, Krishna R.; Yakupitiyage, Amararatne; Soni, Peyush; Bhujel, Ram C.; Thailand (HM Queen) (Pathum Thani, Thailand : Asian Institute of Technology, 2017)
The biofloc and aquamimicry systems had an important foraquaculture all of countries, especially Thailand. The tilapia (Oreochromis niloticus) is the commercial fish in Thailand, and it has higher supply in the local market. The biofloc and aquamimicry technologies can develop the growth performance of them. The substrate as a nitrogen and carbon sources between biofloc and aquamimicry system are different (biofloc; tapioca starch, ammonium chloride and aquamimicry; fermented rice bran) for running the systems during 2 months. The growth performance between biofloc and aquamimicry system were not significantly different (P>0.05), but the aquamimicry system obtained similarresult than biofloc system. The volume of floc or biocolloid also were significantly different among of treatments (biofloc and aquamimicry systems) the floc volume of biofloc higher than aquamimicry system because of smaller particle size of biocolloid and higher density of phytoplankton and zooplankton in the system.The volume of biocolloid in the biofloc system higher than aqaumimicry system. The minimum and maximum of floc volume were 1.40 and 250 ml/L of biofloc system, and for the aquamimicry system were 3.50 and 185 ml/L, respectively,In addition, the volume of flocboth of system were not stable during experiment period. The sludge volume were not significantly different (P>0.05) among of systems. In similar case, the chemical composition of output such as biocolloid, sludge, final fish and water were not significantly different values, but only ash and energy content of sludge and biocolloid were significantly different. The energy of biocolloid were increased following period because of higher density microorganism. Furthermore, the relationship between water quality (DO, pH, alkalinity, TAN, nitrite and nitrate) with biocolloid both of system were had relationship, especially TAN and alkalinity because of substrate for cell bacteria synthesis of heterotrophic bacteria. In addition, the density of zooplankton and phytoplankton also related with the volume of biocolloid and growth performance of tilapia fish.
A thesis submittedin partial fulfillment of the requirements for the degree of Master of Science in Aquaculture and Aquatic Resources Management, School of Environment, Resources and Development
Thesis (M.Sc.) - Asian Institute of Technology, 2017
Keywords: Biocolloids; Fishes -- Growth